Observation and discussion of avalanche electroluminescence in GaN p-n diodes offering a breakdown electric field of 3 MV cm−1. (17th May 2018) - Mandal, S; Kanathila, M B; Pynn, C D; Li, W; Gao, J; Margalith, T; Laurent, M A; Chowdhury, S
Abstract: We report on the first observation of avalanche electroluminescence resulting from band-to-band recombination (BTBR) of electron hole pairs at the breakdown limit of Gallium Nitride p-n diodes grown homo-epitaxially on single crystalline GaN substrates. The diodes demonstrated a near ideal breakdown electric field of 3 MV cm −1 with electroluminescence (EL) demonstrating sharp peaks of emission energies near and at the band gap of GaN. The high critical electric field, near the material limit of GaN, was achieved by generating a smooth curved mesa edge with low plasma damage, using etch engineering without any use of field termination. The superior material quality was critical for such a near-ideal performance. An electric field of 3 MV cm −1 recorded at the breakdown resulted in impact ionization, confirmed by a positive temperature dependence of the breakdown voltage. The spectral data provided evidence of BTBR of electron hole pairs that were generated by avalanche carrier multiplication in the depletion region.